Perception of Bank Customers about Automated Teller Machine (ATM) Service Quality - Dhungel, Amar; Acharya, Banodita; Upadhyay-Dhungel, Kshitiz (Banking Journal, 2012)
DOI: http://dx.doi.org/10.3126/bj.v2i2.6620 Banking Journal, Volume 2 (Issue 2) 22-38